2014
DOI: 10.1177/1708538114537489
|View full text |Cite
|
Sign up to set email alerts
|

Carotid endarterectomy under local and/or regional anesthesia has less risk of myocardial infarction compared to general anesthesia: An analysis of national surgical quality improvement program database

Abstract: Multiple studies have evaluated the effect of anesthesia type on carotid endarterectomy with inconsistent results. Our study compared 30-day postoperative myocardial infarction, stroke, and mortality between carotid endarterectomy under local or regional anesthesia and carotid endarterectomy under general anesthesia utilizing National Surgical Quality Improvement Program database. All patients listed in National Surgical Quality Improvement Program database that underwent carotid endarterectomy under general a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…This difference was largely a result of the increased incidence of MI in the subset of patients with preoperative neurologic symptoms. Kfoury, et al 21 analyzed the results of 42,265 CEA, 11.3% done under RA, from the same database and also found that the incidence of MI was significantly higher in the GA group, (.86% vs .4%, P=.012).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This difference was largely a result of the increased incidence of MI in the subset of patients with preoperative neurologic symptoms. Kfoury, et al 21 analyzed the results of 42,265 CEA, 11.3% done under RA, from the same database and also found that the incidence of MI was significantly higher in the GA group, (.86% vs .4%, P=.012).…”
Section: Discussionmentioning
confidence: 94%
“…Advocates of CAS have contended that this adverse impact on mortality in CEA patients is equally, if not more important than the reduced incidence of periprocedural strokes, most of which are minor. Since the vast majority of CEA in the United States are performed under GA, 19,21 if the periprocedural MI rate when the operation is done under RA is equivalent to that of CAS, then transitioning to more frequent use of RA for CEA would optimize the outcomes for patients undergoing carotid revascularization when compared to CAS. Barriers to this transition are vascular surgeons and anesthesiologists who are comfortable with their present approach, achieve excellent results and thus have little impetus to change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Similarly, two studies of the National Surgical Quality Improvement Program database by Leichtle et al and Kfoury et al suggested increased cardiac morbidity after GA vs RA for CEA. 6,8 Nevertheless, a separate study of the National Surgical Quality Improvement Program database by Schechter et al showed no difference in patient outcomes. 15 Evidence for a link between anesthetic technique and postoperative MI can be found on both sides of the equation, and this study does not offer additional evidence that RA is protective against postoperative MI.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The General Anesthesia versus Local Anesthesia for Carotid Surgery (GALA) trial in 2008 was recognized as a landmark study showing no difference in morbidity or mortality under local anesthesia vs GA. 5 The ideal anesthetic technique, however, has been the subject of intense study, with several studies reporting conflicting results and some suggesting a tendency toward increased cardiac morbidity with GA. [6][7][8][9] Advocates for performing CEA under RA cite reduction in hemodynamic instability and indisputably reliable neurologic monitoring, but many still prefer to employ GA as benefits of RA have not been clearly demonstrated, reliable RA may not be available in all centers, and a certain amount of movement by the patient during the procedure may not be uniformly tolerated.…”
mentioning
confidence: 99%